Corporate governance? : an ethical evaluation of the Second King report in the light of Peter Ulrich's integrative economic ethics - Höver, K. Hendrik W. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2004